Gas source localization with a micro-drone using bio-inspired and particle filter-based algorithms - Neumann, Patrick P.; Hernandez Bennetts, Victor; Lilienthal, Achim J.; Bartholmai, Matthias; Schiller, Jochen H. (Advanced robotics, 2013)
Gas source localization (GSL) with mobile robots is a challenging task due to the unpredictable nature of gas dispersion, the limitations of the currents sensing technologies, and the mobility constraints of ground-based robots. This work proposes an integral solution for the GSL task, including source declaration. We present a novel pseudo-gradient-based plume tracking algorithm and a particle filter-based source declaration approach, and apply it on a gas-sensitive micro-drone. We compare the performance of the proposed system in simulations and real-world experiments against two commonly used tracking algorithms adapted for aerial exploration missions.